A 95-Year Bibliometric Analysis of Spiritual Health Research Within the Scopus Database - Hussein, Siti Zuhaida (Journal of religion and health, 2026)
Spiritual health is a critical dimension of holistic care, encompassing intellectual connectedness and the process of making meaning guided by a transcendent connection. This study conducts a comprehensive bibliometric analysis of spiritual health from 1928 to 2023 using the Scopus database. The aim is to elucidate publication trends, citation metrics, document profiles, country productivity, and keywords in spiritual health research. The data was analyzed using the R and VOSviewer software. A total of 1962 documents were retrieved over 95 years, of which 1650 met the inclusion criteria. The results revealed that up to 2021, these documents encompassed 22,282 citations, averaging 877.98 papers per author. The majority were articles (84.20%) in English (98.88%), primarily within the field of medicine (48.46%). The Journal of Christian Nursing contributed 107 articles, with the most cited document originating from the United States. The overlay visualization map of author keywords displayed prevalent terms such as spiritual care, spirituality, palliative care, nurses, and COVID-19, indicating evolving themes in spiritual health research. In conclusion, this study highlights the important role of spiritual health in holistic care and emphasizes the need to integrate spiritual health into healthcare to meet diverse patient needs.